Capital Structure and its Impact on Financial Performance of Non-Life Insurance Companies of Nepal - Bhattarai, Arasan (Journal of Insurance Studies in South Asia, 2024)
The paper attempts to examine the relationship between capital structure and the financial performance of Nepalese insurance companies. Return on assets and earnings per share are the dependent variables. Independent variables are total debt ratio, equity to total assets ratio, size, leverage and tangibility. This paper uses descriptive as well as causal comparative research design to examine the general structure of capital structure and financial performance and their relationship. The data were collected from annual reports of listed insurance companies in Nepal. The study is based on 36 observations from 6 non-life insurance companies of Nepal from 2073/74 to 2078/79. The regression models are estimated to test the effect on financial performance variables i.e. return on assets and earnings per share. The result shows that insurance companies having a high firm size have better financial performance. An increase in firm size increase return on assets and an increase in equity. Larger companies, despite their size advantages, may experience challenges in maintaining high profitability. This suggests that an excessively leveraged capital structure can hinder financial performance in terms of ROA.The impact of the asset tangibility, equity to total asset on earning per share is positive and there is the negative impact of debt ratio, leverage on earning per share. Lower ROA directly translates to lower EPS, impacting shareholder returns. Companies with higher asset tangibility may experience higher EPS, indicating the importance of asset quality in generating shareholder value. The major conclusion of this study is that the insurance companies of Nepal interested to increase financial performance can increase their size and decrease debt ratio, leverages. Nepalese general insurance companies should carefully manage their capital structure, avoiding excessive debt levels and leverage to maintain profitability and enhance shareholder value. Strategies to improve asset quality and increase asset tangibility can positively influence EPS and overall financial performance. Continuous monitoring and adjustment of capital structure based on market conditions and performance metrics are essential for sustainable growth and competitiveness in the insurance industry in Nepal.